EFEKTIVITAS MADU DALAM PERAWATAN LUKA PADA PASIEN DIABETES MELLITUS: A LITERATURE REVIEW - Enggelina Anjani Kaeng; Haryanto Haryanto (Jurnal Keperawatan dan Kesehatan, 2022)
Abstract Background: The prevalence of Diabetes Mellitus (DM) in Indonesia continues to increase and according to The International Diabetes Federation (IDF) in 2017 Indonesia was ranked 6th in the world with a total of 10.3 million diabetes cases, which is estimated to increase to 16.7 million in 2045. Purpose: to see the effectiveness of honey in healing foot wounds Diabetes Mellitus. Method: Journal search was conducted electronically using several databases, such as Google Scholar, Pubmed, with keywords used were honey, wounds, and Diabetes and obtained a total of 6 journals. Results: From the results of a review of 4 journals that honey is effective in inhibiting bacterial colonization and accelerating wound healing in people with diabetes mellitus. Conclusion: Honey therapy is effective in healing diabetes mellitus wounds.